2017
DOI: 10.1002/hed.24909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of definitive chemoradiotherapy for cervical esophageal cancer: Comparison of failure pattern and toxicities between intensity‐modulated radiotherapy and 3‐dimensional conformal radiotherapy

Abstract: The IMRT group was comparable with 3D conformal RT group, with a better salvage rate. We recommend extended cervical irradiation for nodal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…18 However, the prevalence of radiation-related complication with induction chemoradiotherapy in the current literature varies widely. [19][20][21] There is still a lack of evidence and controversy comparing IMRT with 3D-CRT for LANPC. To the best of our knowledge, there is no randomized controlled comparison for IMRT vs. 3D-CRT in LANPC treated with IC-CCRT bringing about acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, the prevalence of radiation-related complication with induction chemoradiotherapy in the current literature varies widely. [19][20][21] There is still a lack of evidence and controversy comparing IMRT with 3D-CRT for LANPC. To the best of our knowledge, there is no randomized controlled comparison for IMRT vs. 3D-CRT in LANPC treated with IC-CCRT bringing about acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT and 3D-CRT have been demonstrated an improved treatment outcome and lower skin toxicity in other head and neck cancer, they are the primary radiotherapy techniques for cancer patients during recent decades [18]. However, the prevalence of radiation-related complication with induction chemoradiotherapy in the current literature varies widely [19][20][21]. There is still a lack of evidence and controversy comparing IMRT with 3D-CRT for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no statistically significant difference observed in OS, local FFS, and regional FFS between the IMRT group and two-dimensional conformal radiotherapy group in the study conducted by Cao et al [25]. A recent published data from Japan [26] showed that IMRT achieved a significantly better 3-year OS than 3D-CRT (81.6% vs. 57.2%, p=0.037). They found that the sufficient salvage rate was higher in IMRT than 3D-CRT group when locoregional recurrence was presented, which contributed to the difference in OS.…”
Section: Discussionmentioning
confidence: 81%